The Future Knowledge Worker: an Intercultural Perspective - LEON, Ramona-Diana (Management Dynamics in the Knowledge Economy, 2015)
The paper aims to provide empirical evidence regarding the influence of cultural specificity on the capacity of the European higher education institutions of developing the future knowledge workers. Therefore, an exploratory research is employed and the qualitative approach is combined with the qualitative one. The focus is on the European business faculties since they are the main provider of the advanced economies workforce. 24 units of analysis are selected based on five criteria: university’s number of students, research level, experience on the market, presence on QS Worlds University Ranking, position occupied in national ranking and access to information; for each of them, a content analysis is applied. Then, a logistic regression analysis is employed in order to determine whether cultural dimensions (independent variables) influence the use of a specific teaching activity, the development of certain skills and faculties’ capacity of developing the future knowledge workers (dependent variables). The results show that power distance and uncertainty avoidance may decrease the odds of developing the future European knowledge worker while the long term orientation may increase these odds. All five clasical dimensions of Hofstede influence the development of graduates’ skills but only four of them have an impact on the teaching and evaluating activities, namely: power distance, individualism, masculinity and uncertainty avoidance; the second one influences academics’ attitude towards increasing the use of practical activities within the courses while the other ones have an impact on the theoretical activities.